The effect of stimulus context on the buildup to stream segregation - Sussman-Fort, Jonathan; Sussman, Elyse (Frontiers in Neuroscience, 2014)
Stream segregation is the process by which the auditory system disentangles the mixture of sound inputs into discrete sources that cohere across time. The length of time required for this to occur is termed the ‘buildup’ period. In the current study, we used the buildup period as an index of how quickly sounds are segregated into constituent parts. Specifically, we tested the hypothesis that stimulus context impacts the timing of the buildup and, therefore, affects when stream segregation is detected. To measure the timing of the buildup we recorded the Mismatch Negativity component (MMN) of event-related brain potentials (ERPs), during passive listening, to determine when the streams were neurophysiologically segregated. In each condition, a pattern of repeating low (L) and high (H) tones (L-L-H) was presented in trains of stimuli separated by silence, with the H tones forming a simple intensity oddball paradigm and the L tones serving as distractors. To determine the timing of the buildup, probe tones occurred in two positions of the trains, early (within the buildup period) and late (past the buildup period). The context was manipulated by presenting roving versus non-roving frequencies across trains in two conditions. MMNs were elicited by intensity probe tones in the Non-Roving condition (early and late positions) and the Roving condition (late position only) indicating that neurophysiologic segregation occurred faster in the Non-Roving condition. This suggests a shorter buildup period when frequency was repeated from train to train. Overall, our results demonstrate that the dynamics of the environment influence the way in which the auditory system extracts regularities from the input. The results support the hypothesis that the buildup to segregation is highly dependent upon stimulus context and that the auditory system works to maintain a consistent representation of the environment when no new information suggests that reanalyzing the scene is necessary.